Function and Strength after Free Abdominally Based Breast Reconstruction: A 10-Year Follow-Up. Issue 1 (January 2019) - Nelson, Jonas A.; Tecci, Michael G.; Lanni, Michael A.; Fischer, John P.; Fosnot, Joshua; Selber, Jesse C.; Wu, Liza C.; Serletti, Joseph M.
Abstract : Background: The long-term impact of abdominally based free flap breast reconstruction is incompletely understood. The aim of this study is to provide long-term, subjective and objective health data on abdominally based free flap breast reconstruction patients, with specific attention to the effects of laterality, flap type, and obesity. Methods: Patients were enrolled in this prospective study between 2005 and 2010 and completed preoperative, early (<1 year), and long-term (5 to 10 years) evaluations. Objective examination included an assessment of upper and lower abdominal function and a functional independence measure. Patient-reported outcomes included the 36-Item Short-Form Health Survey and the BREAST-Q abdominal well-being module. Scores were compared by laterality (unilateral versus bilateral), flap type (muscle-sparing free transverse rectus abdominis musculocutaneous versus deep inferior epigastric artery perforator), and presence of obesity. Results: Fifty-one patients were included, with an average 8.1-year follow-up. Overall, 78.8 percent of patients had stable or improved scores across the upper and lower abdominal function and functional independence measures, and minimal objective differences across flap laterality or types were observed. Postoperative scores improved for 36-Item Short-Form Health Survey physical health ( p < 0.001) and mental health ( p < 0.001), and did not differ based on laterality or flap type. Obesity negatively impacted physical health ( p = 0.002) and mental health ( p = 0.006). Conclusions: Abdominally based autologous breast reconstruction is associated with significant improvements in long-term quality of life across key domains of physical and mental health with little functional impairment and no long-term differences across flap type or laterality. Obese patients, however, may be at risk for subjective physical and mental health impairment, perhaps unrelated to the surgery itself. Abstract : Supplemental Digital Content is available in the text.